Cancer-associated fibroblasts in desmoplastic tumors: emerging role of integrins. (May 2020) - Zeltz, Cédric; Primac, Irina; Erusappan, Pugazendhi; Alam, Jahedul; Noel, Agnes; Gullberg, Donald
Abstract: The tumor microenvironment (TME) is a complex meshwork of extracellular matrix (ECM) macromolecules filled with a collection of cells including cancer-associated fibroblasts (CAFs), blood vessel associated smooth muscle cells, pericytes, endothelial cells, mesenchymal stem cells and a variety of immune cells. In tumors the homeostasis governing ECM synthesis and turnover is disturbed resulting in abnormal blood vessel formation and excessive fibrillar collagen accumulations of varying stiffness and organization. The disturbed ECM homeostasis opens up for new types of paracrine, cell-cell and cell-ECM interactions with large consequences for tumor growth, angiogenesis, metastasis, immune suppression and resistance to treatments. As a main producer of ECM and paracrine signals the CAF is a central cell type in these events. Whereas the paracrine signaling has been extensively studied in the context of tumor-stroma interactions, the nature of the numerous integrin-mediated cell-ECM interactions occurring in the TME remains understudied. In this review we will discuss and dissect the role of known and potential CAF interactions in the TME, during both tumorigenesis and chemoresistance-induced events, with a special focus on the "interaction landscape" in desmoplastic breast, lung and pancreatic cancers. As an example of the multifaceted mode of action of the stromal collagen receptor integrin α11β1, we will summarize our current understanding on the role of this CAF-expressed integrin in these three tumor types.